Recycling derelict land - Fleming, Derek (Telford, 1991)
Provides engineers with a basis on which to classify types of derelict land, and alert them to the range of environmental and legal considerations involved. This book examines the hazards involved in land recycling, and includes flow charts that clarify the steps required in selecting the final solutions to problems of contamination.